2008
DOI: 10.1002/iub.56
|View full text |Cite
|
Sign up to set email alerts
|

What controls TOR?

Abstract: SummaryThe target of rapamycin (TOR) is a protein kinase with numerous functions in cell growth control. Some of these functions can be potently inhibited by rapamycin, an immunosuppressive and potential anticancer drug. TOR exists as part of two functionally distinct protein complexes. The functions of TOR complex 1 (TORC1) are effectively inhibited by rapamycin, but the mechanism for this inhibition remains elusive. The identification of TORC2 and recent reports that rapamycin can inhibit TORC2 functions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 144 publications
1
42
0
Order By: Relevance
“…The mTORC1 signaling pathway is a complex regulatory mechanism that can sense and respond to the availability of nutrients, energy, stress, and mitogens to modulate protein synthesis (21,22,27). Upon its activation, mTORC1 catalyzes the phosphorylation of S6K1 at its Thr-389 residue leading to its activation, which in turn phosphorylates rpS6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mTORC1 signaling pathway is a complex regulatory mechanism that can sense and respond to the availability of nutrients, energy, stress, and mitogens to modulate protein synthesis (21,22,27). Upon its activation, mTORC1 catalyzes the phosphorylation of S6K1 at its Thr-389 residue leading to its activation, which in turn phosphorylates rpS6.…”
Section: Resultsmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR), a key Ser-Thr kinase highly conserved from yeast to mammals, exists intracellularly in two functionally distinct complexes, mTORC1 and mTORC2 (21)(22)(23). mTORC1 consists of the mTOR catalytic subunit and associated proteins raptor, PRAS40, and mLST8/ G␤L.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that inhibition of mTOR intrinsic catalytic activity cannot explain the mechanism of action of rapamycin or amino acid withdrawal on mTOR-mediated signaling (45). Thus, alternate mechanisms have been postulated (46). Rapamycin binding could theoretically hinder reception of upstream activating signals or impair access of docked substrates to the mTOR catalytic domain without affecting mTOR intrinsic catalytic activity; alternatively, rapamycin binding could lead to activation of a phosphatase that dephosphorylates mTORC1 substrates (47).…”
mentioning
confidence: 99%
“…Cellular mTOR regulation remains incompletely defined, however (13,24,31). mTOR senses and integrates signals from diverse environmental cues such as growth factors and hormones (i.e., insulin, insulin-like growth factor [IGF], and epidermal growth factor [EGF]), nutrients (i.e., amino acids and glucose), and cellular stresses (15,22,34,53,72). mTOR interacts with different partner proteins to form at least two functionally distinct signaling complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) (2,4).…”
mentioning
confidence: 99%